2020
DOI: 10.21203/rs.3.rs-25602/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased salt tolerance in Zymomonas mobilis strain generated by adaptative evolution

Abstract: BackgroundEthanologenic alphaproteobacterium Zymomonas mobilis has been acknowledged as a promising biofuel producer. There have been numerous efforts to engineer this species applicable for an industrial-scale bioethanol production. Although Z. mobilis is robustly resilient to certain abiotic stress such as ethanol, the species is known to be sensitive to saline stress at a mild concentration, which hampers its industrial use as an efficient biocatalyst. To overcome this issue, we implemented laboratory adapt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
3
3
Order By: Relevance
“…This was somewhat contrary to what we anticipated, since Zs100 cells underwent long cultivation under constant stress, which could have in uenced its metabolism or growth pro le for better survival. This result is in sharp contrast to our previous experience with Z. mobilis adaptive evolution against abiotic stress, in which 10-20 passages of serial transfer drove strains to gain adapted phenotype [19]. The obtained result here showed that the competition with yeast in the co-culture did not in uence Z. mobilis ethanologenic physiology.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This was somewhat contrary to what we anticipated, since Zs100 cells underwent long cultivation under constant stress, which could have in uenced its metabolism or growth pro le for better survival. This result is in sharp contrast to our previous experience with Z. mobilis adaptive evolution against abiotic stress, in which 10-20 passages of serial transfer drove strains to gain adapted phenotype [19]. The obtained result here showed that the competition with yeast in the co-culture did not in uence Z. mobilis ethanologenic physiology.…”
Section: Resultscontrasting
confidence: 99%
“…Whole genome of the co-cultured Z. mobilis strains was sequenced by GATC re-sequencing service (INVIEW Genome sequencing). The reference sequence was our lab stock Zm6 strain which was previously sequenced [18,19].…”
Section: Whole Genome Sequencingmentioning
confidence: 99%
“…This was somewhat contrary to what we anticipated, since Zs100 cells underwent long cultivation under constant stress, which could have in uenced its metabolism or growth pro le for better survival. This result is in s sharp contrast to our previous experience with Z. mobilis adaptive evolution against abiotic stress, in which 10-20 passages of serial transfer drove strains to gain adapted phenotype [20]. The obtained result here showed that the competition with yeast in the co-culture did not in uence Z. mobilis ethanologenic physiology.…”
Section: Resultscontrasting
confidence: 99%
“…This was somewhat contrary to what we anticipated, especially in the Z. mobilis cells with S. cerevisiae in 100 g/L glucose, since the Z. mobilis cells in that condition underwent long cultivation under constant stress, which could have influenced its metabolism or growth profile for better survival. This result is in sharp contrast to our previous experience with Z. mobilis adaptive evolution against salt stress, in which 10-20 passages of serial transfer drove the strains to gain adapted phenotype of two times better total ethanol production under the saline condition than that of the parental strain [ 19 ]. The obtained result here showed that the competition with yeast or E. coli in the co-culture did not influence Z. mobilis ethanologenic physiology.…”
Section: Main Textcontrasting
confidence: 94%
“…Whole genome of the co-cultured Z. mobilis strains was sequenced by GATC re-sequencing service (INVIEW Genome sequencing). The reference sequence was our lab stock Zm6 strain which was previously sequenced [ 18 , 19 ].…”
Section: Main Textmentioning
confidence: 99%